2019
DOI: 10.1038/s41467-018-07987-0
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-3 links HSF1 and YAP/TAZ signalling to control aggressive behaviours in cancer-associated fibroblasts

Abstract: Aggressive behaviours of solid tumours are highly influenced by the tumour microenvironment. Multiple signalling pathways can affect the normal function of stromal fibroblasts in tumours, but how these events are coordinated to generate tumour-promoting cancer-associated fibroblasts (CAFs) is not well understood. Here we show that stromal expression of Dickkopf-3 (DKK3) is associated with aggressive breast, colorectal and ovarian cancers. We demonstrate that DKK3 is a HSF1 effector that modulates the pro-tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 48 publications
8
119
1
Order By: Relevance
“…Intriguingly, in contrast to those earlier studies (Azzolin et al, 2014;Ferrari et al, 2019), the authors now showed that LRP6…”
contrasting
confidence: 95%
See 1 more Smart Citation
“…Intriguingly, in contrast to those earlier studies (Azzolin et al, 2014;Ferrari et al, 2019), the authors now showed that LRP6…”
contrasting
confidence: 95%
“…The initial observation that LRP6 downregulation and Hippo activation co-occur upon nutrient starvation motivated the authors to address whether LRP6 regulates Hippo signaling. Several studies have already demonstrated that LRP6 inactivates Hippo signaling, at least in part through interfering with the interaction between YAP/TAZ and the b-catenin destruction complex (Azzolin et al, 2014;Ferrari et al, 2019). Using YAP phosphorylation, localization, and transcriptional activity as functional readouts for Hippo signaling output, Jeong et al confirmed that LRP6 is a negative regulator of the Hippo pathway and modulates Hippo signaling activity in response to nutrient levels.…”
mentioning
confidence: 99%
“…Physiological stress is also another factor contributing to stromagenesis. Heat shock factor 1 (HSF1), which responds in part to protein misfolding, is required for the generation of CAFs 67,68 . Physiological and genomic stresses can also trigger changes in fibroblasts.…”
Section: What Is the Origin Of Cafs?mentioning
confidence: 99%
“…It has been proposed that the DKK3-Kremen-1 interaction may affect Wnt signaling (46). Nicola confirmed that Kremen-1, but not Lipoprotein receptor-related protein 6 (LRP6), immunoprecipitated with DKK3 in cancer-associated fibroblasts, and the mRNA levels of Kremen-1 were not altered after DKK3 silencing (47). In the present study, Kremen-1 did not show any change in expression during the same timeframe when DKK3 levels were observed to be reduced after ICH.…”
Section: Discussionmentioning
confidence: 93%